2009
DOI: 10.1108/16605370910948821
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis of organizational commitment, job involvement and job satisfaction in Turkish hospitality industry

Abstract: Purpose -This paper aims to determine the structural relationships between job involvement, job satisfaction, and three dimensions of organizational commitment (i.e. affective commitment, normative commitment, and continuance commitment) in the Turkish hospitality industry.Design/methodology/approach -A questionnaire survey was conducted among the full-time employees of five-star hotels in the Antalya region, which is an important tourism destination especially for Europeans and Russians in Turkey.Findings -Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 37 publications
4
40
0
2
Order By: Relevance
“…employees feel as though they should remain in the organization because they 'owe it' to their current employer. Mathieu and Zajac (1990), Cohen (2000), and Ketchand and Strawser (2001), had their work deconstructed by Kuruüzüm et al (2009) who posited the view that job involvement has a stronger relationship with both affective and normative commitment, than it has with continuance commitment. Based on the theoretical foundations laid by earlier work investigating these relationships (Allen & Meyer, 1990;Hackett, Bycio, & Hausdorf, 1994;Hartmann & Bambacas, 2000;Tayyeb & Riaz, 2004), which found the stronger relationships between job involvement and affective and normative commitment, we developed the following hypotheses:…”
Section: Job Involvement and Organizational Commitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…employees feel as though they should remain in the organization because they 'owe it' to their current employer. Mathieu and Zajac (1990), Cohen (2000), and Ketchand and Strawser (2001), had their work deconstructed by Kuruüzüm et al (2009) who posited the view that job involvement has a stronger relationship with both affective and normative commitment, than it has with continuance commitment. Based on the theoretical foundations laid by earlier work investigating these relationships (Allen & Meyer, 1990;Hackett, Bycio, & Hausdorf, 1994;Hartmann & Bambacas, 2000;Tayyeb & Riaz, 2004), which found the stronger relationships between job involvement and affective and normative commitment, we developed the following hypotheses:…”
Section: Job Involvement and Organizational Commitmentmentioning
confidence: 99%
“…In a similar vein Paullay, Alliger, and Stone-Romero (1994) suggest that an integral part of employees' self-definition is the degree to which they are involved in their job. Consequently, highly-job-involved employees are more committed to their organization, invest substantial effort in order to achieve organizational objectives (Ineson, Benke, & Laszlo, 2013;Rotenberry & Moberg, 2007), and are thus less likely to turnover (Kanungo, 1979;Kuruüzüm, Cetin, & Irmak, 2009;Pfeffer, 1994). Utilizing these constructs, and by synthesizing critically the work of Greenhaus (1971), Gordon, Philpot, Burt, Thompson, and Spiller (1980), and Morrow (1983), Blau (1985) makes a case for the relationship between these aspects of job involvement and organizational commitment.…”
Section: Job Involvement and Organizational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Kord and Tamini (2012) concurrently confirmed that organizational commitment is significantly correlated to job satisfaction. The results of Kuruüzüm, Çetin, and Irmak (2009) have shown that job affective commitment, and normative commitment increase job satisfaction. Based on the above studies, it seems that highly committed individuals tend to be more satisfied.…”
Section: Organizational Commitment and Job Satisfactionmentioning
confidence: 86%
“…The findings supported this hypothesis. According to Yiing and Ahmad (2009);Anari (2012); Yucel and Bektas (2012); Kord and Tamini (2012) and Kuruüzüm et al (2009), there is a significant and positive association between organizational commitment and job satisfaction. The association between job characteristics and job satisfaction, which was hypothesized by H3, was also accepted.…”
Section: Discussionmentioning
confidence: 99%